2015
DOI: 10.1002/celc.201500098
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Platinum in the Operational Range of Fuel Cells

Abstract: One of the most important practical issues in low‐temperature fuel‐cell catalyst degradation is platinum dissolution. According to the literature, it initiates at 0.6–0.9 VRHE, whereas previous time‐ and potential‐resolved inductively coupled plasma mass spectrometry (ICP–MS) experiments, however, revealed dissolution onset at only 1.05 VRHE. In this manuscript, the apparent discrepancy is addressed by investigating bulk and nanoparticulated catalysts. It is shown that, given enough time for accumulation, trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
193
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(208 citation statements)
references
References 71 publications
14
193
1
Order By: Relevance
“…The dramatic ECSA reduction for Pt/C in Figure 1E (estimated on the basis of the initial mass of Pt in the catalyst layer) is thus related to particle detachment due to carbon corrosion, whereby smaller nanoparticles exhibit an increased probability to detach, 21 and not to other ECSA decreasing mechanisms leading to Pt nanoparticle growth (see below). Specifically, the negligible impact of these nanoparticle-aggregation routes is likely related to the potential regime applied in the start-stop AST (i.e., 1.0-1.5 V RHE ), which does not include sufficiently low potentials that would lead to the reduction (and dissolution/redeposition) [42][43][44] of the Pt-(hydr)oxides passivating the nanoparticles' surface.…”
Section: Resultsmentioning
confidence: 99%
“…The dramatic ECSA reduction for Pt/C in Figure 1E (estimated on the basis of the initial mass of Pt in the catalyst layer) is thus related to particle detachment due to carbon corrosion, whereby smaller nanoparticles exhibit an increased probability to detach, 21 and not to other ECSA decreasing mechanisms leading to Pt nanoparticle growth (see below). Specifically, the negligible impact of these nanoparticle-aggregation routes is likely related to the potential regime applied in the start-stop AST (i.e., 1.0-1.5 V RHE ), which does not include sufficiently low potentials that would lead to the reduction (and dissolution/redeposition) [42][43][44] of the Pt-(hydr)oxides passivating the nanoparticles' surface.…”
Section: Resultsmentioning
confidence: 99%
“…18 In this case the amount of dissolved material is controlled predominantly by the diffusion of dissolved species from the electrode to the bulk electrolyte, which must be comparable for both electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…13 More recently, studies have emerged related to the potentiostatic and potential cycling dissolution of polycrystalline platinum, 4,[14][15][16][17] single crystal platinum, 18 platinum black, 19 nano-particle films, [20][21][22] and of nano-particle platinum supported on high surface area carbon (Pt/C). 17,[23][24][25][26][27] These studies were motivated by the desire to determine the origins of the observed loss of electrochemically-active surface area (ECA) of phosphoric acid fuel cell and polymer electrolyte fuel cell (PEFC) electrocatalysts, as this is a dominant cause of irreversible loss of Pt/C-based cathode performance. [28][29][30][31][32][33][34] A comprehensive review of platinum dissolution in the context of the fuel cell application was recently published.…”
mentioning
confidence: 99%